(untitled) (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2023)
The topic of this article is relevant at the present time, because Surveys are currently a very popular method of collecting marketing information, and the data obtained during the survey allows us to reduce the degree of uncertainty associated with making marketing decisions.